Anemia Prevention Program for Adolescent Girls in Indonesia During the Covid-19 Pandemic - Rabia Wahdah; Sulistyaningsih Sulistyaningsih (Universitas Andalas, 2021)
Background: Anemia in adolescents is one of the world's health problems to date, even during the Covid-19 pandemic. Adjustments to the anemia prevention program for adolescents must be carried out considering that the Covid-19 pandemic is still ongoing. Objective: To investigate the anemia prevention program for adolescents during the Covid-19 pandemic. Methods: This study is a Scoping Review consisting of 5 stages including identification of questions with the PEOS framework (Population, Exposure, Outcomes, Study design), identification of relevant articles, search of relevant articles through topic-related information, databases of PubMed, Scopus, ScienceDirect, and Grey Literature (Google Scholar), literature searching strategy, and the last stage of article selection. Results: From a total of 268 articles identified based on themes, there were 5 relevant studies related to the topic including the anemia prevention program, namely the program of iron tablet supplementation in schools, the organization of anemia webinars, online socialization of anemia, and the use of the DR'E-Dumind education model as an anemia prevention education model as well as anemia prevention obstacles which got several anemia prevention programs carried out by optimizing the use of online media. Conclusion: The anemia prevention program during the pandemic was carried out by optimizing the use of online educational media